KEANEKARAGAMAN DAN POTENSI JAMUR MAKRO DI KAWASAN SUAKA MARGASATWA BUKIT RIMBANG BUKIT BALING (SMBRBB) PROPINSI RIAU, SUMATERA - Noverita Noverita; Dennys Perdana Armanda; Ikhsan Matondang; Tatang Mitra Setia; Ratna Wati (Jurnal Pro-Life, 2019)
The Bukit Rimbang Bukit Baling Wildlife Reserve Area (SMBRBB) Riau is one of the areas that has the characteristics of lowland rainforest types with high biodiversity, so it is possible to find many macro fungi, but there is no data on macrofungi diversity. This research was conducted with the aim of obtaining diversity data and potential data on macrofungi, both as food ingredients and as medicinal ingredients. This study uses a searching method that is modified by the path method using sample plots. 138 macrofungi species were obtained, which included 52 genera, 37 families and 3 phyla. Macrofungi diversity index at this location is relatively moderate, and high uniformity index. 66 species potentially as medicinal ingredients, including Amauroderma rugosum, Ganoderma aplanatum, Ganoderma lucidum, Lentinus sajo-caju, Lentinus squamolosus, Cymatoderma elegans, Daldinea concentrica, Microporus xantopus, M. afinitis, Pycnoporus cinnabarius, Polyporus arcularius, Rigidoporus microporus, Rigidoporus microporus, Trametes versikularis, and Xylaria longipes. As many as 32 species have potential as food ingredients, including Auricularia auricula, Auricularia delicata, Auricularia polytricha, Cookeina sulcipes, Phallus indusiatus, Lentinus sajor-caju, Lentinus squamolosus, Pleurotus ostreatus, Schizophyllum commune, Tramella fuciformis, and Volvariellavolvacea. Keywords: cultivation, diversity, food, makrofungi, medicine.